2018
DOI: 10.1021/acsomega.8b02447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydration on the Structure of Reline Deep Eutectic Solvent: A Molecular Dynamics Study

Abstract: In this article, we have performed an all-atom molecular dynamics simulation study to investigate the influence of water on the molecular level arrangement of reline deep eutectic solvent for different hydration levels ranging from 3.4 to 58.1 wt % of water and complemented the observations of recently measured neutron scattering experimental data. This study is particularly important because water is being introduced as a second hydrogen bond donor/acceptor in reline, wherein the structure is primarily govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 65 publications
(145 reference statements)
15
139
0
Order By: Relevance
“…41 Our results further indicate that water preferentially solvates the Cl – anion over cation. 41 This can be seen also by the HB networks between water molecules and the species of DESs, which are presented in Figure S10 of the Supporting Information. It is found that EG makes approximately 0.7 HBs per EG with the anions in the absence of water, whereas the addition of 80% of water greatly decreases this to 0.04 HBs per EG molecule.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…41 Our results further indicate that water preferentially solvates the Cl – anion over cation. 41 This can be seen also by the HB networks between water molecules and the species of DESs, which are presented in Figure S10 of the Supporting Information. It is found that EG makes approximately 0.7 HBs per EG with the anions in the absence of water, whereas the addition of 80% of water greatly decreases this to 0.04 HBs per EG molecule.…”
Section: Resultssupporting
confidence: 56%
“…27 Recently, the influence of the hydration of different DESs was investigated using MD simulations, particularly focusing on static properties including densities, RDFs, spatial distributions, and hydrogen bonding. 3941 Baz et al 42 performed MD simulations to compute static and dynamic properties of glyceline–water mixtures at various temperatures. The simulations were additionally supported by equation-of-state modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that H 2 O content significantly influences the interactions of DES constituents (water, choline, urea, chloride and nickel) [41,44,45]. Therefore, it is known that the increase of water content from 0.1 wt% to 2.1 wt% (or to 0.25 wt% in blank electrolyte) changes the interactions between water and DES components by possibly increasing the electrolyte integrity, which occurs by strengthening the Ch þ -Cl e interactions [42]. This could cause the shift of Ni 2þ reduction to more negative potentials upon presence of small amounts of water (up to $2-3 wt%).…”
Section: Resultsmentioning
confidence: 99%
“…Only System 2 (choline chloride/imidazole) showed an energy value below 5 eV. Among systems containing triphenylmethylphosphonium bromide, System 5 was of interest, showing an indirect band gap of 3.74 eV, similar to other known semiconductors [30][31][32][33]. To date, 3.74 eV is the lowest value of an energy band gap ever reported for such kind of systems.…”
Section: Of 11mentioning
confidence: 90%